The Effects of Training on Knowledge and Beliefs About Breast Cancer and Early Diagnosis Methods Among Women - YILMAZ, MERYEM; SAYIN, Yazile; SAYIN, YAZİLE; Cengiz, Hatice Oner (My University, 2017)
Objective: Breast cancer (BC) is the most common female malignancy in the world and Turkey. Its prevalence and mortality are surprisingly increasing at a rapid rate. The objective of this study was to determine the effectiveness of training sessions on women-s knowledge of relevant risk factors of BC and screening methods, screening behaviors and health beliefs among of healthy women in Turkey.